Enhanced light trapping in polycrystalline silicon thin-film solar cells using plasma-etched submicron textures - Huang, Ying; Sahraei, Nasim; Widenborg, Per I.; Peters, Ian Marius; Dalapati, Goutam Kumar; Iskander, Aneesa; Aberle, Armin G. (Solar Energy Materials and Solar Cells, 2014)
In this work a highly scattering rear Si surface texture (RST) is realized by plasma etching of polycrystalline silicon (poly-Si) thin-film solar cells on glass. The resulting RST shows reflection haze values of more than 95% at the Si-air interface. The average feature size of the texture is around 200 nm. We use a model based on the scalar scattering theory to calculate the scattering properties of the textured surface. We also use a commercial thin-film solar cell simulator to evaluate the light trapping and current enhancement induced by the texture. Combining this submicron RST with a micrometer-scale glass texture can produce a multi-scale rear Si surface texture. Assuming a 1900 nm thick poly-Si solar cell on glass with a high-quality back surface reflector (silicon dioxide/silver stack), the calculated photon density absorbed in the poly-Si solar cell with the multi-scale rear Si surface texture corresponds to a 1-sun short-circuit current density (jsc) of 31.1 mA/cm2, which is 1 mA/cm2 more than the calculated jsc of a poly-Si solar cell with the same thickness on textured glass but without RST. The calculated current densities do not fu lly take current loss due to parasitic absorption into consideration, hence are slightly overestimated. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Light trapping; Plasma etching; Scalar scattering theory; Silicon texture; Thin-film solar cells